- #1

- 30

- 0

## Homework Statement

## Homework Equations

## The Attempt at a Solution

Last edited:

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter lola1990
- Start date

- #1

- 30

- 0

Last edited:

- #2

- 22,129

- 3,297

Do you know the chinese remainder theorem??

- #3

- 22,129

- 3,297

What bothers you about it??

- #4

- 22,129

- 3,297

So I already proved that I+J=R, so that there are x in I and y in J such that x+y=1. Then, f(x)=(I, 1+J) because x is in I and x=1-y which is in 1+B. Similarly, f(y)=(1+I, J). Now, consider kx+ry. f(kx+ry)=f(k)f(x)+f(r)f(y)=(k+I, k+J)(I, 1+J)+(r+I, r+J)(1+I, J)=(I, k+J)+(r+I)(J)=(r+I)(k+J). Is that right?

The bolded part have a wrong notation. It must be (r+I,J) and (r+I,k+J). But it is correct.

Share: